Vulnerability of Farmer Households in the Eruption-Prone Area of Mount Merapi - Yunita Khusnul Khotimah; Hasna Fajar Suryani (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2026)
The eruption causes social crises, hunger, damage to regional spatial planning, degradation of environmental quality, disruption of daily activities, damage to facilities, and agricultural losses. Most of the livelihoods of the population in the Mount Merapi area are farmers. Farmers' vulnerability increases due to eruptions, necessitating identification, anticipation, and mitigation to prevent exacerbation. The purpose of this study is to identify the vulnerability index of farmer households affected by the eruption in the Mount Merapi area. This research was conducted in Selo Sub-district, Boyolali Regency, and Kemalang Sub-district, Klaten Regency, which are prone areas affected by the eruption. The analysis method used was descriptive. Descriptive analysis was used to identify the vulnerability index of farmer households affected by the eruption in the Mount Merapi area using the Livelihood Vulnerability Index. The results indicated that the component value in the Selo sub-district for the socio-demographic profile was 0.127, livelihood 0.66, health 0.035, social network 0.45, food 0.17, water 0.30, and natural disaster 0.027. The component values in the Kemalang sub-district for the socio-demographic profile are 0.125 for livelihood, 0.66 for health, 0.14 for social network, 0.14 for food, 0.93 for water, and 0.017 for natural disaster. Kecamatan Kemalang, Klaten Regency, is more vulnerable than Kecamatan Selo, Boyolali Regency. Kecamatan Kemalang's LVI index is 0.357 greater than Kecamatan Selo's 0.251. The government needs to provide training for farmers on disaster management during eruptions, such as livestock evacuation and post-harvest management for horticultural commodities. Farmers should also participate in government-provided livestock insurance to reduce losses.